Critical success factors for campus interaction spaces and services – a systematic literature review. Issue 2 (27th January 2020) - Jansz, Sascha Naomi; van Dijk, Terry; Mobach, Mark P.
Abstract : Purpose: The purpose of this paper is to create an overview of current literature and identify gaps in what is known about stimulating interaction through spaces and services provided on university campuses. Design/methodology/approach: The authors used the preferred reporting items for systematic reviews and meta-analyses (PRISMA) statement methodology for systematic literature review. In total, 3, 616 articles were screened, 31 articles were included. Facility Directors from 13 Dutch Universities were asked to define the search terms related to services. Findings: Spaces and services were mostly studied separately. The majority of papers (18/31) were based on perceptions (surveys or interviews). The following critical success factors were identified in the literature: geographic proximity, cognitive proximity, scale, transitional spaces, comfort and experience, shared facilities and events, local buzz and networks. These factors are interrelated. The authors present a new relational model, from spaces and services, through interaction to innovation, visualising how the identified papers are related. Research limitations/implications: The scope of possible findings may have been narrowed because prior relevant studies were rather limited and as a consequence of the search strategy designed to limit the number of unrelated hits. Some knowledge gaps may not have been identified, as only a few mainstream concepts related to the critical success factors were used for comparison. Nevertheless, the literature review provides a reliable overview of current academic knowledge regarding critical success factors for spaces and services that stimulate interaction on campuses. Originality/value: This paper offers a novel perspective by emphasising the relational chain from interaction to innovation, visualising the large diversity in research fields and summarising the critical success factors in the literature.